The Issues and Tendencies of Arts Education Modernization in the Republic of Kazakhstan - Zolotareva, L.; Rezin, Zh.; Karipbayev, Zh.; Burtibayeva, A.; Bodikov, S. (Published by Canadian Center of Science and Education, 2015)
The paper is concerned with development strategy of the national educational system in the Republic of Kazakhstan, principal development trends of arts education in the Republic of Kazakhstan in terms of apprehension of the national tradition based on UNESCO recommendations stated in “Road Map for Arts Education”, adopting the idea of ethnocultural education; the basic content of the “Art education in the Republic of Kazakhstan: apprehension of national traditions and rapprochement of cultures” scientific and analytical report is analyzed; national policy in the area of art education in Kazakhstan, cultural heritage preservation and development are considered; training of Bachelors of Fine Arts in the area of education is represented; modern benchmarks in “Art History of Kazakhstan”, formation of multicultural personality are shown; modernization problems of arts education in Kazakhstan and its study prospects are stated: promotion of creative potential, increase in education and culture status in the 21th century is a complicated and critical task that forecasts the following prospects: interrelation of arts education and current social problems of society; increase in public information awareness and explanation of value and social significance of arts and artistic and pedagogic education; creation of demand for arts education and qualified arts teachers in the modern educational system; universalization of arts teachers’ professional training; intensification and expansion of researches in the area of arts education and sharing creative knowledge at the international level; financing fiscal studies in this area. Conclusions: so far considerable experience has been gained in the area of arts education with regard to ethnocultural tradition, that allows the Kazakh system of arts education to gradually carry out the process of entering world educational space.
Keywords: the Republic of Kazakhstan; arts education; cultural heritage preservation and development; ethnocultural education and cultivation; modernization